Snow cover and snow-albedo changes in the central Andes of Chile and Argentina from daily MODIS observations (2000-2016) - Malmros, Jeppe K.; Mernild, Sebastian H.; Wilson, Ryan; Tagesson, Torbern; Fensholt, Rasmus (My University, 2018)
The variables of snow cover extent (SCE), snow cover duration (SCD), and snow albedo (SAL) are primary factors determining the surface energy balance and hydrological response of the cryosphere, influencing snow pack and glacier mass-balance, melt, and runoff conditions. This study examines spatiotemporal patterns and trends in SCE, SCD, and SAL (2000-2016; 16 years) for central Chilean and Argentinean Andes using the MODIS MOD10A1 C6 daily snow product. Observed changes in these variables are analyzed in relation to climatic variability by using ground truth observations (meteorological data from the El Yeso Embalse and Valle Nevado weather stations) and the Multivariate El Nino index (MEI) data. We identified significant downward trends in both SCE and SAL, especially during the onset and offset of snow seasons. SCE and SAL showed high inter-annual variability which correlate significantly with MEI applied with a one-month time-lag. SCE and SCD decreased by an average of similar to 13 +/- 2% and 43 +/- 20 days respectively, over the study period. Analysis of spatial pattern of SCE indicates a slightly greater reduction on the eastern side (similar to 14 +/- 2%) of the Andes Cordillera compared to the western side (similar to 12 +/- 3%). The downward SCE, SAL, and SCD trends identified in this study are likely to have adverse impacts on downstream water resource availability to agricultural and densely populated regions in central Chile and Argentina.
Keywords: andes; argentina; chile; climate change; enso; mod10a1; modis; snow albedo; snow cover extent; time series analysis